2022
DOI: 10.3389/fpls.2022.979956
|View full text |Cite
|
Sign up to set email alerts
|

ROS scavenging and ion homeostasis is required for the adaptation of halophyte Karelinia caspia to high salinity

Abstract: The halophyte Karelinia caspia has not only fodder and medical value but also can remediate saline-alkali soils. Our previous study showed that salt-secreting by salt glands is one of main adaptive strategies of K. caspia under high salinity. However, ROS scavenging, ion homeostasis, and photosynthetic characteristics responses to high salinity remain unclear in K. caspia. Here, physio-biochemical responses and gene expression associated with ROS scavenging and ions transport were tested in K. caspia subjected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 97 publications
1
9
0
Order By: Relevance
“…An earlier study by Li et al (2022) revealed that high salt tolerance was conferred by the synergistic contribution of ROS scavenging mechanisms and Na + /K + transport to redox balance and ion homeostasis. Overexpression of CeqHAK6 and CeqHAK11 increased the K + /Na + ratio and antioxidant enzyme activity of plants, which in turn reduced the accumulation of malondialdehyde, cations and H 2 O 2 due to membrane peroxidation, and finally achieved the purpose of protecting membrane structure and alleviating the damage caused by salt stress to the plants.…”
Section: Discussionmentioning
confidence: 99%
“…An earlier study by Li et al (2022) revealed that high salt tolerance was conferred by the synergistic contribution of ROS scavenging mechanisms and Na + /K + transport to redox balance and ion homeostasis. Overexpression of CeqHAK6 and CeqHAK11 increased the K + /Na + ratio and antioxidant enzyme activity of plants, which in turn reduced the accumulation of malondialdehyde, cations and H 2 O 2 due to membrane peroxidation, and finally achieved the purpose of protecting membrane structure and alleviating the damage caused by salt stress to the plants.…”
Section: Discussionmentioning
confidence: 99%
“…When plants are exposed to a saline environment, ROS overgeneration disrupts the balance between ROS production and scavenging, inducing the oxidative damage of cells (Hao et al, 2021). Halophytes evolve a multifaceted antioxidant defense network to reduce ROS overgeneration under abiotic stress (Sirin and Aslım, 2019;Li et al, 2022). The phenylpropanoid pathway involves the biogenesis of diverse phenolic polymers, such as flavonoids and phenolic acids, which play important roles of ROS scavenging in plant defense against abiotic stresses (Liu et al, 2020;Li et al, 2021a).…”
Section: Flavonoids and Phenolic Acids Positively Dominate The Salt R...mentioning
confidence: 99%
“…To produce salt-tolerant crops, we need to change our perspective and focus on traits that were ignored during the domestication of staple crops. These traits include keeping redox balance and signaling ROS mechanisms effectively, which are common in salt-tolerant plants [ 28 ].…”
Section: Introductionmentioning
confidence: 99%